(Dis)continuation of care of the pre-term newborn at the border - Rosilene Berres; Maria Aparecida Baggio (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to understand how continuation of care for the preterm newborn in the health care network at the border. Methods: the Grounded Theory was the methodological framework. Data were collected through 17 semi-structured interviews between July 2016 and March 2017. Results: "Describing the structure and functioning of the Child Nutrition Center" represents the context; "Experiencing and signifying premature birth" are the causal conditions; "Identifying conditions that intervene in the process of continuation of care for the preterm newborn" are the intervening conditions; "Ensuring continuation of care for the preterm newborn" are strategies; "Identifying (dis)continuation of care flows for the preterm newborn at the border" are the study's consequences and phenomenon. Final Considerations: there is a need to plan referral and counter-referral flows of the preterm newborn and the commitment of public health managers to ensure continuation of care.